Analisis Wacana Feminisme Dalam Novel Bak Rambut Dibelah Tujuh Karya Muhammad Makhdlori Serta Implikasinya Terhadap Pembelajaran Bahasa Dan Sastra Indonesia Di SMA - Sitohang, Hanna; Panggabean, Sarma; Simaremare, Juni Agus (Lembaga Riset dan Inovasi Almatani, 2024)
This study aims to describe the portrayal of women in the novel Bak Rambut Dibelah Tujuh by Muhammad Makdlori. The method used in this study is qualitative research method. This study analyzes and describes the portrayal of women (feminism) in novels, the most dominant position between the subject-object position in and the position of the reader in Muhammad Makhdlori's Bak Rambut Dibelah Tujuh Novel and the implications of research results in learning Indonesian Language and literature in Senior High School. Data collection techniques in this study used recording techniques. The results obtained in this study are as follows: (1) The depiction of women in Muhammad Makhdlori's Novel Bak Rambut Dibelah Tujuh. (2) the most dominant position between the subject-object position and the reader's position in Muhammad Makhdlori's novel Bak Rambut Dibelah Tujuh. (3) Implications of research results on learning Indonesian Language and Literature in Senior High School.